2015
DOI: 10.1038/bmt.2015.122
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of pre-transplant quality of life in allogeneic hematopoietic cell transplantation recipients

Abstract: Quality of life (QOL) is an important outcome for hematopoietic cell transplantation (HCT) recipients. Whether pre-HCT QOL adds prognostic information to patient and disease related risk factors has not been well described. We investigated the association of pre-HCT QOL with relapse, non-relapse mortality (NRM), and overall mortality after allogeneic HCT. From 2003 to 2012, the Functional Assessment of Cancer Therapy-Bone Marrow Transplant Scale instrument was administered before transplantation to 409 first a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
1
20
2
Order By: Relevance
“…As in our study, the pre‐HCT PCS was strongly correlated with the pretransplant KPS, but the latter did not predict survival as an independent factor. A single‐center study of 409 allogeneic HCT recipients by Hamilton et al showed that the Trial Outcome Index and the physical well‐being subscales of the FACT‐BMT were associated with mortality after transplantation. Our results extend these findings and suggest that the prognostic value of PRO measures holds true in the real‐world setting of HCT across multiple centers …”
Section: Discussionmentioning
confidence: 99%
“…As in our study, the pre‐HCT PCS was strongly correlated with the pretransplant KPS, but the latter did not predict survival as an independent factor. A single‐center study of 409 allogeneic HCT recipients by Hamilton et al showed that the Trial Outcome Index and the physical well‐being subscales of the FACT‐BMT were associated with mortality after transplantation. Our results extend these findings and suggest that the prognostic value of PRO measures holds true in the real‐world setting of HCT across multiple centers …”
Section: Discussionmentioning
confidence: 99%
“…According to the reported articles, posttransplant CMV reactivation would increase NRM and influence survival in patients receiving allogeneic HSCT [ 12 , 28 30 ]. In addition, pretransplant comorbidities and quality of life were also important factors for HSCT recipients [ 31 ]. Hence, the additional influence of posttransplant CMV reactivation, history of type 2 diabetes mellitus, and smoking history were also evaluated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies have shown that QOL before transplant for hematological malignancies is associated with post transplant mortality even when accounting for patients' performance status and comorbidities. 20,21 Moreover, patients with advanced solid malignancies place as high a value on optimizing their QOL as to other goals of therapy such as extending their life as much as possible. 29,30 Our data begs the question whether the possibility of cure that is unique to patients with advanced hematologic malignancies such as high-risk MDS trumps QOL concerns in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown that QOL scores before allogeneic HCT are independently associated with post-transplant mortality irrespective of performance status and medical comorbidities. [20][21][22] Moreover, while patients' and clinicians' perception of QOL may influence their decisions regarding pursuit of therapies, 22 the impact of baseline QOL on the likelihood of receiving allogeneic HCT for advanced MDS is not known.…”
Section: Introductionmentioning
confidence: 99%